Financial development and TFP growth: Cross-country and industry-level evidence - Francisco Arizala; Eduardo Cavallo; Arturo Galindo (Inter-American Development Bank, Research Department, 2009)
This paper estimates the impact of financial development on industry-level total factor productivity (TFP) growth using a largely unexploited panel of 77 countries with data for 26 manufacturing industries for the years 1963 to 2003. A significant relationship is found between financial development and industry-level TFP growth when controlling for country-time and industry-time fixed effects. The results are both statistically and economically significant. TFP growth can accelerate up to 0.6 percent per year, depending on the external finance requirement of industries, following a one standard deviation increase in financial development. The results are robust to different samples and specifications.
Keywords: D24; E44; O47; 330; Financial development; TFP growth; Volatility; Produktivität; Kreditmarkt; Wirtschaftswachstum; Finanzsektor; Vergleich; Welt